Five historical views on the new evangelization - Verdoy, Alfredo (Razón y fe, 2018)
This text presents five historical views on evangelization and the mission of the Church. Five historical moments in which the fervor, the preaching, the apostolic leadership of religious and priests knew how to bring the Christian people to the person of Christ and from him build a Christian society. Five historical moments in which the laity, as time passed, took a greater role in the new evangelization of the Church.